Pulp Termo Mekanis (TMP) dan Kimia Termo Mekanis (CTMP) dari Limbah Batang Kenaf Pulps from TMP and CTMP of Kenaf Stem Residue - Wawan K Haroen (Masyarakat Peneliti Kayu Indonesia, 2008)
Pulps from thermo mechanical pulping (TMP) are produced by applying elevated temperatures and physical treatment in the process through mechanical energy. A study on the TMP and CTMP processes have been conducted on the residue of Kenaf stems wood. The general pulping conditions of CTMP process are impregnated with Sodium Hydroxide (NaOH) and steamed, while TMP are steamed both for 30 minutes at temperature 120ºC, and steam pressure 1.5 atm. Average of pulp yields are TMP 91.29% and CTMP 86.16% and fractionations of fiber pulp was analyzed by using of Bauer McNett fractionators which fiber contents more than 78% at 200 mesh. Pulp bleaching with Hydrogen Peroxide or peroxide bleaching was carried out in two phase P1 and P2. The pulp brightness pulp in the range 70 76 % ISO and fulfil the physical strength properties for Newspaper requirements according to Indonesian National Standard (SNI .14.0091 – 1998). The energy consumption of Kenaf stem’s chips refining for TMP process is 4.75 kWh/kg dry chips and for CTMP process 2.7 kWh/kg dry chip. The consumption of energy for CTMP process is 50% lower compared with the energy consumed for the TMP process.